Computational insights into inhibiting EphA2: Integrating structure-based virtual screening, docking, and molecular dynamics simulations for small molecule discovery: Identifying Inhibitor against EphA2 - Mohd Nehal; Jahanarah Khatoon; Salman Akhtar; Ahmad Khan, Mohd Kalim (Cellular and Molecular Biology, 2024)
Elevated expression and dysfunction of ephrin type A receptor-2 (EphA2) have been implicated in the initiation and progression of cancer, metastasis, and unfavorable clinical outcomes. A promising strategy to counteract this dysregulation involves the development of small-molecule inhibitors that target EphA2. Our study focuses on this objective. To initiate Structure-Based Virtual Screening (SBVS), we leveraged an advanced online platform, the Mcule database, which houses an extensive collection of millions of chemical compounds. Using drug similarity filters, we efficiently identified ten thousand potential hits. By further refining the selection through toxicity profiling, we prudently narrowed down the candidates to a more manageable set of 100 molecules. Using the Mcule Single Click, DockThor, and SwissDock tools, we conducted multi-scoring docking assessments of thirty-seven compounds that satisfied the ADME standards. A comprehensive evaluation of Gibbs binding free energy terms, as derived from these docking tools, facilitated the identification of top-ranking docking hits. Remarkably, among the known inhibitors, dasatinib displayed the most robust binding to EphA2 with an average ΔG of -9.0 kcal/mol. Intriguingly, alternatives have emerged in recent years. Notably, small molecules such as Mcule-1579910267 (ΔG: -9.3 kcal/mol), Mcule-1893218381 (ΔG: -9.2 kcal/mol), Mcule-3981378344 (ΔG: -9.3 kcal/mol), and Mcule-8617639093 (ΔG: -9.1 kcal/mol) exhibited a notably strong binding affinity to EphA2, rivaling dasatinib. Subsequently, the four leading ligands along with dasatinib were selected for the MD simulations. Our rigorous analyses during the MD simulation phase encompassing RMSD, RMSF, SASA, ΔGsolv, and Rg underscored the favorable stability of Mcule-8617639093. This compelling evidence ultimately signifies the potential for selective EphA2 inhibition.